The Effect of Feel Experience and Action Experience on Repurchase Interest at Nest Coffee Jombang During the COVID-19 Pandemic - Mela Sri Rahayu; Mar'atul Fahimah (INCOME: Innovation of Economics and Management, 2022)
Café is a type of restaurant but prioritizes a relaxed atmosphere, entertainment and comfort. So that cafe managers need to pay attention to the variety of menus, attractive interior designs for today's teenagers and also entertaining live music so as to improve the lifestyle of today's teenagers. This study aims to analyze how much influence feel experience and action experience have on repurchase interest at Nest Coffee Jombang. In this study, the sampling method used was purposive sampling technique, for the sample size used was 100 respondents according to the criteria determined by the researcher, questionnaires were used for the data collection process in this study. This data retrieval using multiple linear regression analysis techniques, validity test, reliability test, T test, and F test.